FORMULASI LOTION TABIR SURYA EKSTRAK KULIT PISANG Goroho (Musa acuminafe sp) MENGGUNAKAN KONSENTRASI TWEEN 80 DAN SPAN 80 - Olii, Audia Triani; Mursyid, Mumtihanah; Mokodompit, Sukma Meilinda (PHARMACY UMI JOURNAL SYSTEM, 2024)
Flavanoids are compounds that have activity as sunscreen. This compound is contained in banana peels and can be used as sunscreen ingredients. The purpose of this research is to optimize the preparation of goroho banana peel extract lotion (Musa acuminafe sp). The use of certain combinations of Tween 80 and Span 80 in lotion preparations has been reported to be able to form an optimal in-water oil-type emulsion. Formula optimization with various variations of Tween 80 and Span 80 concentrations using Design expert version 10 of the Simplex Lattice Design model with pH parameters, viscosity, adhesion, spreadability and SPF determination. The optimal lotion formula was obtained at the use of Tween 80 4.5% and Span 80 5.5%. The optimal formula has a pH of 5.46, a viscosity of 33226.66 dPas, a adhesion of 6.01 seconds, a spread of 6.25 cm/s, and an SPF test and has good asceptability to respondents. The optimal formula of software prediction results with research results shows insignificant differences. This shows that the Simplex Lattice Design method can be used to predict the physical properties parameters of goroho banana peel extract lotion preparations.